Pathomorphological changes of capillaries in the cerebral cortex in type 2 diabetes mellitus - V. O. Tumanskyi; Yu. M. Avramenko (Zaporozhye State Medical University, 2021)
The aim of the study was to determine microscopic, immunohistochemical, electron microscopic, morphometric parameters of capillaries in the cerebral cortex in deceased patients with type 2 diabetes mellitus (DM) in comparison with the conditional control group and the group of deceased patients with dyscirculatory ischemic encephalopathy. Materials and methods. Microscopic, immunohistochemical, electron microscopic and morphometric studies of the cerebral cortex capillaries were performed in 3 groups: group I - 20 deceased patients with type 2 DM, group II conditional control (CC) - 20 deceased patients without clinical morphological signs of DM and cerebrovascular pathology, group III - 20 patients with dyscirculatory ischemic encephalopathy (DIEP). Results. It was found that in type 2 DM, the capillaries in the cerebral cortex lose pericytes due to their apoptosis: the number of pericytes in the cortical capillaries in type 2 DM was statistically significantly lower by 57.14 % compared to CC group and 50.00 % lower compared to DIEP group, the level of caspase-3 expression in the cortical microvessels in type 2 DM was significantly higher by 230.85 % compared with CC group and 81.67 % higher than in DIEP group. According to electron microscopy in type 2 DM, apoptosis of pericytes and single endothelial cells in the cerebral cortex capillaries was determined as well as significant expansion of basement membranes with the accumulation of electron-dense amorphous material and collagen fibrils. According to the results of morphometry, the outer diameter of the cortical capillaries in type 2 DM group was 4.90 % significantly larger, the inner diameter was 9.78 % smaller and the walls were 66.62 % thicker (compared with CC group) due to the accumulation of PAS-positive substances of blood serum and fibrosis, confirmed by 22.96 % greater area of type IV collagen expression in the microvessel walls. Conclusions. The pathomorphological changes of microvessels identified in deceased patients with type 2 diabetes mellitus are signs of diabetic cerebral microangiopathy.